2010
DOI: 10.1007/s11060-010-0210-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetic analysis of methotrexate administered directly into the fourth ventricle in a piglet model

Abstract: We have developed a piglet model to assess chemotherapy administration directly into the fourth ventricle as a potential treatment for medulloblastoma and other malignant posterior fossa tumors. The objective of this study was to assess safety and pharmacokinetics after methotrexate infusions into the fourth ventricle. Catheters were inserted into the fourth ventricle and lumbar cistern in five piglets. Two milligrams of Methotrexate (MTX) was infused into the fourth ventricle on five consecutive days. Safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…the delivery of active agents directly into the CSF, has gained renewed attention as an approach that could circumvent systemic barriers to CNS drug delivery. IT administration achieves high concentrations of drug in the CSF that bathes the brain and spinal cord with minimal systemic exposure 16 . However, poor drug solubility, inadequate pharmacokinetics, limited tissue distribution, and neurotoxicity remain significant obstacles for most IT administered agents 712 .…”
Section: Introductionmentioning
confidence: 99%
“…the delivery of active agents directly into the CSF, has gained renewed attention as an approach that could circumvent systemic barriers to CNS drug delivery. IT administration achieves high concentrations of drug in the CSF that bathes the brain and spinal cord with minimal systemic exposure 16 . However, poor drug solubility, inadequate pharmacokinetics, limited tissue distribution, and neurotoxicity remain significant obstacles for most IT administered agents 712 .…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, novel treatment approaches should achieve both local and regional tumor control while minimizing systemic drug exposure, as metastatic disease outside of the central nervous system (CNS) is rare. Previous studies in piglets and non-human primates demonstrated that a catheter can be safely placed into the fourth ventricle and that chemotherapy can be infused without causing new neurological deficits or other recognized toxicity [ 7 10 ]. These infusions yielded high drug levels in the fourth ventricle as well the spinal subarachnoid space that are maintained for at least 24 h with undetectable or negligible systemic drug levels [ 7 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trough CSF methotrexate levels were nearly 80-fold higher (median 3.18 µmol/L) than serum levels. It would be expected based upon prior animal studies that peak methotrexate levels, which were not measured in the current study, would likely have been several orders of magnitude higher than trough levels [ 7 , 9 , 10 ]. Ideally, methotrexate distribution would be assessed by lumbar spine CSF, but these were not performed to avoid lumbar punctures that would not have affected the patients’ plan of care.…”
Section: Discussionmentioning
confidence: 99%
“…However, placement of a VAD into the fourth ventricle for administration of chemotherapy or novel agents may be most logical at the time of initial resection when the only remaining known disease is tumor that is adherent to the floor of the fourth ventricle. Previous animal studies suggest that drug administration into the fourth ventricle at that time would yield high drug levels at the site of residual disease as well as regional distribution to CSF spaces throughout the neuraxis [ 12 14 ]. Future studies will include placement of VADs into the fourth ventricle at the time of initial surgical resection for administration of intraventricular chemotherapy postoperatively in selected patients.…”
Section: Discussionmentioning
confidence: 99%